Witnessing “imperfect victims”: (In)culpability, collaboration, and the “suffering subject” - HUSSAIN, SALMAN (American ethnologist, 2022)
After the 9/11 attacks, Pakistan's military government unleashed a program of extrajudicial detentions to surveil and track down “Islamic terrorists.” These men are known as the “missing” or “disappeared” persons in the movement mobilized by their families to protest the abductions. Ethnographic research with the families of “missing persons” in Pakistan, however, involves working with people whom I call “imperfect victims”—that is, persons who do not easily fit the subject position of those occupying the “suffering slot.” Such imperfect victims often rely on nonnormative ethics of grief and sacrifice to help them make sense of violence stemming from larger political‐economic structures of power. An ethnography of imperfect victims responds to calls for going beyond the “suffering subject” in anthropology. It does so by questioning the humanitarian assumption in anthropology that suffering is a common, apolitical ground for all humanity and that a politics of solidarity can be built on the suffering of others. [ witnessing , suffering subject , ethnography , human rights , disappearances , missing persons , Pakistan , South Asia ]